The issue of school privatisation in Côte d'Ivoire - KOUTOU, N’Guessan Claude; GOIN BI, Zamble Théodore (Advances in Social Sciences Research Journal, 2020)
The Ivorian state has been involved in the construction of public schools given their importance for development. Since the 1980s, there has been a reduction in funding linked to the economic crisis and structural adjustment programmes. Thus, by a convention the State will concede the public service of education to the private sector. The results of this research on the conditions of access to private schools in the Abidjan district were analysed through a cross-sectional study with descriptive and analytical aims. This has led to disparities in costs between municipalities. 40,000 FCFA for minima and 1, 922,000 FCFA for maxima, a multiplication order of 48. In secondary school, the minimum is 43,000 FCFA and the maximum is 2, 706,000 FCFA, a multiplication order of 63. In higher education there are less disparities. In total, there are many differences in the costs of schooling from one school to another. While the public-private partnership has encouraged more children to attend school, it has also created a challenge to access because of the expensive costs of attending school.